Evaluation of the relationship between milk consumption and dental caries in 3-5 years old children in Ray city - J. Mahmodian; Naghavi; H. Nekoie (Tehran University of Medical Sciences, 1994)
Undoubtedly, Tooth decay is still one of the most significant problems in human communities. Tooth decay is defined as a microbial disease that causes demineralization of hard tissues and degradation of organic components of teeth. Although there are various theories on etiology of dental caries, Miller's acidogenic theory (1890) and Gottileb's proteolitic theory (1933) have gained the most credibility among the others. In general, status and amount of saliva, oral hygiene, tooth structure, type and quantity of microorganisms and diet are the most important factors that can lead to tooth decay. Since the manner and type of child nutrition during infancy is considered as a significant factor in development and progression of dental caries and also there has not been published any research on this subject in Iran yet, this study was designed and carried out to find the association between the type of milk intake in infancy and the rate of dental caries in 3-5 year old children.